11C-Methionine Positron Emission Tomography/Computed Tomography Versus 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in Evaluation of Residual or Recurrent World Health Organization Grades II and III Meningioma After Treatment. Issue 4 (July 2018) - Tomura, Noriaki; Saginoya, Toshiyuki; Goto, Hiromi
Abstract : Objective: The aim of this study was to determine the assessment of positron emission tomography–computed tomography using 11 C-methionine (MET PET/CT) for World Health Organization (WHO) grades II and III meningiomas; MET PET/CT was compared with PET/CT using 18 F-fluorodeoxy glucose (FDG PET/CT). Methods: This study was performed in 17 cases with residual and/or recurrent WHO grades II and III meningiomas. Two neuroradiologists reviewed both PET/CT scans. For agreement, the κ coefficient was measured. Difference in tumor-to-normal brain uptake ratios (T/N ratios) between 2 PET/CT scans was analyzed. Correlation between the maximum tumor size and T/N ratio in PET/CT was studied. Results: For agreement by both reviewers, the κ coefficient was 0.51 ( P < 0.05). The T/N ratio was significantly higher for MET PET/CT (3.24 ± 1.36) than for FDG PET/CT (0.93 ± 0.44) ( P < 0.01). 11 C-methionine ratio significantly correlated with tumor size ( y = 8.1 x + 16.3, n = 22, P < 0.05), but FDG ratio did not Conclusions: 11 C-methionine PET/CT has superior potential for imaging of WHO grades II and III meningiomas with residual or recurrent tumors compared with FDG PET/CT.